Localization of β2-Glycoprotein 1 in Late Endosomes of Human Endothelial Cells - Dunoyer-Geindre, S.; Kruithof, E. K. O.; Rochemonteix, Galve-de B.; Rosnoblet, C.; Gruenberg, J.; Reber, G.; de Moerloose, P. (Thrombosis and Haemostasis, 2001)
Antiphospholipid antibodies (APLA) are associated with thrombophilia and recurrent pregnancy loss. Different mechanisms have been proposed to explain their pathogenic effects and among them, we have previously shown that APLA accumulate in late endosomes of human umbilical vein endothelial cells (HUVEC) leading to a redistribution of the cation-independent mannose-6-phosphate receptor (CI-M6PR). Because many APLA are directed towards β2-glycoprotein 1 (β2GP1)-phospholipid complexes, we investigated the localisation of β2GP1 in HUVEC. By immunofluorescence analysis, using monoclonal and polyclonal anti- β2GP1 antibodies, we detected β2GP1 at the cell surface and in late endosomes. Incubation of HUVEC with anti- β2GP1 antibodies resulted in antibody accumulation at the cell surface and within late endosomes and in a redistribution of the CI-M6PR from the Golgi apparatus to late endosomes. The anti- β2GP1 antibodies remained detectable in late endosomes even after several days of incubation in antibody-free medium. The accumulation of anti- β2GP1 antibodies in late endosomes of endothelial cells and the resulting modification of intracellular protein trafficking may contribute to the pathogenic effects of these antibodies.
Keywords: β2-glycoprotein 1; late endosomes; endothelial cells; anti-phospholipid antibodies